Collective and individual DC pension schemes: comparing benefit amounts received by members - Gierusz, Anna (Zbiorowy a indywidualny program emerytalny o zdefiniowanej składce: porównanie świadczeń uzyskanych przez uczestników, 2017)
Occupational pension schemes in Poland are all defined contribution (DC) in nature. The contribution amount is fixed, whereas the benefit amount is unknown and depends on many factors such as contributions paid and investment returns received. The risk in a DC scheme is borne by the member, who may not be equipped with the financial knowledge needed to manage such a risk. A solution applied by some countries takes the form of collective DC schemes, where the risk is borne collectively by all members of such a scheme. The aim of this paper is to describe collective DC schemes functioning in selected countries and to compare the benefit amounts which the members can receive from collective and from individual DC schemes. The results show that the variability of benefit amounts in a collective DC scheme is lower than in a traditional DC scheme. An additional safeguard, which allows to improve the financial condition of a collective DC scheme in cases of low investment returns has been proposed
Nauki o Finansach = Financial Sciences, 2017, Nr 4 (33), s. 62-72
Keywords: occupational pension schemes; defined contribution pension schemes; collective DC schemes; pracownicze programy emerytalne; programy emerytalne o zdefiniowanej składce; programy zbiorowe DC